2013
DOI: 10.1371/journal.pone.0079037
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lung Injury and Acute Kidney Injury Are Established by Four Hours in Experimental Sepsis and Are Improved with Pre, but Not Post, Sepsis Administration of TNF-α Antibodies

Abstract: IntroductionAcute kidney injury (AKI) and acute lung injury (ALI) are serious complications of sepsis. AKI is often viewed as a late complication of sepsis. Notably, the onset of AKI relative to ALI is unclear as routine measures of kidney function (BUN and creatinine) are insensitive and increase late. In this study, we hypothesized that AKI and ALI would occur simultaneously due to a shared pathophysiology (i.e., TNF-α mediated systemic inflammatory response syndrome [SIRS]), but that sensitive markers of ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 39 publications
5
52
0
Order By: Relevance
“…1A). These findings are consistent with other studies reporting markedly reduced glomerular filtration rate and elevated BUN with 4 hours of endotoxin exposure in mice (Bhargava et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…1A). These findings are consistent with other studies reporting markedly reduced glomerular filtration rate and elevated BUN with 4 hours of endotoxin exposure in mice (Bhargava et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…Experimental studies showed that TNF-a plays a role in the early pathogenesis of sepsis-related-AKI. 28,29 Clinical studies revealed that IL-6, procalcitonin (PCT) can be used as a predictive marker for sepsis-related-AKI in patients with sepsis. 30,31 In accordance with these studies, we showed that baseline NLR is fruitful and strong predictor of sepsis-related-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…While detection of acute lung injury is not easy in early stages, the authors suggested that it can indicate severity of sepsis. [26] Increased levels of BUN and creatinine were used to define AKI. Craciun et al reported that creatinine is a predictor of glomerular filtration rate, which, though influenced by factors such as gender and age, can be used to detect AKI.…”
Section: Discussionmentioning
confidence: 99%